PENGARUH CAPITAL INTENSITY DAN THIN CAPITALIZATION TERHADAP NILAI PERUSAHAAN DENGAN TAX AVOIDANCE SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BEI PERIODE 2017-2020 - Aniatun, Novita; Perwitasari W., Dwi; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2022)
Automotive companies are one type of business that is growing rapidly in Indonesia. Automotive companies are one of the companies listed on the Indonesia Stock Exchange and are considered more productive and can provide a wide chain effect so as to increase the added value of raw materials, increase labor, produce foreign exchange sources, and the largest contributors to taxes and customs. The purpose of this study is to find out the influence of Capital intensity and Thin capitalization on the Company's Value with Tax avoidance as an intervening variable in Automotive Companies listed on the IDX for the period 2017-2020. The population of this study is many as 13 companies. Sampling techniques are determined by Purposive Sampling. Data analysis and hypothesis testing in this study using the Structural-Partial Least Square Equation Method (PLS-SEM). The results of the test hypothesis of direct influence using the Smart PLS 3.0 application, showed that Capital intensity has a significant positive effect on Tax avoidance, Thin capitalization has a positive but insignificant effect on Tax avoidance, Capital intensity has a negative effect on company value, Thin capitalization has a significant negative effect on company value, and Tax avoidance has a positive but insignificant effect on the value of the company. The results of the indirect influence hypothesis test show capital intensity has a positive but insignificant effect on the value of the company and thin capitalization has a positive but insignificant effect on the company's value.